ISLAM DAN PENDIDIKAN: STUDI PEMIKIRAN MOHAMMAD HATTA - Fuady, Ahmad Syauqi (At-Tuhfah : Jurnal Studi Keislaman, 2019)
This paper is a literature study using a historical approach that takes primary and secondary data from the writings of Mohammad Hatta, autobiography, and writing about Mohammad Hatta. Hatta was one of the important figures for the birth of the Republic of Indonesia who participated in the independence struggle. Hatta is also known as a thinker whose broad spectrum includes economics, philosophy, ideology, politics, social, culture, religion, and education. Religion became an integral part of Hatta since childhood. Islam for Hatta became the basis of personal values ​​that guide behavior. Likewise, religion has a role in developing social, political, and social life. Hatta's Islamic thought style was more substantially patterned, rather than formative. Education was also an identical part of Hatta since the struggle for Indonesian independence. The political task in the main colony is to educate the people to understand their duties, rights, and responsibilities so that new cadres of leaders can be born. After Indonesia's independence, the issue of education became one of the concerns of Hatta. Education for an independent country is an investment in the future of a country.